Game-practicing as Socio-Psychological Training for Adaptation of Migrants: Background and Research - A. Ruonala, Lydia; I. Mironova , Oksana (International Journal of Psychosocial Rehabilitation, 2020)
The European migrant crisis has presented a challenge to the scientific community to study migration processes, adaptation of migrants and society to each other and methodology of these processes. The study aims at distinguishing the socio-psychological factors of successful migrants’ adaptation. The methods of research are theoretical analysis of the problem, the method of expert evaluation and factor analysis of the data. The results have confirmed the existing hypothesis that the following requirements should be taken into account for the socio-psychological training: to support the work with clients’ traumatic experience through the symbolic space; to be a platform for the dialogue between the local population and visitors; to answer questions, linking the client with the meaning-forming characteristics of individuals and the article pays special attention to the prerequisites for the adaptation and psychological board game in order to form a symbolic transition space for cross-cultural dialogue and increase knowledge about the adaptation processes both for the migrants themselves and for the local population.